Bacteriophage Types and Antibiotic Susceptibility of Staphylococcus aureus - Klastersky, J. (1971)
In vitro tests of 132 strains of Staphylococcus aureus, among which were 38 (28.7%) heteroresistant strains, were performed with 14 commonly used antibiotics, including gentamicin and vancomycin. Heteroresistant strains were found predominantly, but not only, with group 3 phage-typable strains; no heteroresistant strain was found in out-patients. Gentamicin appeared as a uniformly effective agent at low concentrations against oxacillin-sensitive and -resistant strains. It is suggested that gentamicin should be compared to vancomycin in future clinical therapeutic trials in severe staphylococcal infections, especially in cases due to oxacillin-resistant strains.